A low-alloy high-carbon martensite steel with 2.6 GPa tensile strength and good ductility. (1st October 2018) - Wang, Yingjun; Sun, Junjie; Jiang, Tao; Sun, Yu; Guo, Shengwu; Liu, Yongning
Abstract: A low-alloy and high-carbon martensite steel (0.66% C) with ultrafine grains is produced by combination of Tempforming (tempering and deforming of a quenched steel) and reheating followed by water quenching and low temperature tempering. The size of prior-austenite grains of the steel is reduced to 2.4 μm through this new technique, and its ultimate tensile strength of 2.6 GPa and elongation of 7% are obtained, which is the highest strength in low alloy high strength steels. The microstructure of the high carbon martensite consists of high density dislocations, undissolved spherical carbides, and dispersed nano-scale Fe3 C and Fe5 C2 phases precipitated at interior of martensitic after tempering. The strengthening mechanisms of the ultrafine grain martensitic steel are mainly dislocation strengthening and precipitation strengthening and also fine grain strengthening. The tensile strength and ductility of the steel are superior to that of existing maraging steels, such as C350, the highest strength in commercialized level, in which more than 20% precious alloy elements such as Co, Mo, Ni, and Ti are contained, and the cost of our materials is only about 1/50 of the C350. All above advantages are desirable for broad industrial applications at an economic cost. Graphical abstract: Image 1